A new path for small producers against Covid-19 (Research, Society and Development, 2020)
The objective of this article is to analyze how small producers are organizing themselves to market their products, in face of the covid-19. Researches were carried out in bibliographic collections and interviews with the members of the whatsapp group. The research is characterized as exploratory and descriptive with a qualitative approach. Data collection occurred through the aid of an online questionnaire using the Google Forms platform. Among the results obtained, it was found that the creation of the group triggered the commercialization of its products, as a result of the use of cell phones and the strengthening of reciprocity relations between small producers in order to be able to sell their goods.